Peripouch Fat Area Measured on MRI Image and Its Association With Adverse Pouch Outcomes. Issue 4 (1st March 2018) - Gao, Xian Hua; Chouhan, Hanumant; Liu, Gang Lei; Lan, Nan; Remer, Erick; Stocchi, Luca; Ashburn, Jean; Hull, Tracy L; Shen, Bo
Abstract: Background: There are no published studies on the impact of peripouch fat on pouch outcomes in inflammatory bowel disease (IBD) patients. Methods: Patients with pelvic MRI-DIXON scans from our prospectively maintained Pouch Database between 2002 and 2016 were evaluated. Peripouch fat area was measured on MRI-DIXON-F images at the middle height level of the pouch (area M) and the highest level of the pouch (area H). Results: Of all 1863 patients in the database, 197 eligible patients were included in this study. The median of area M was 52.4 cm 2, so the 197 patients were classified into 2 groups: group 1 (Area-M <52.4 cm 2 ) and group 2 (Area-M ≥52.4 cm 2 ). Compared with group 1, group 2 was found to have thicker perianal fat, more Caucasian and more males. Group 2 also had a higher Area-H, more weight, height, and body mass index, along with greater age at IBD diagnosis, age at pouch construction and pouch age, and a higher frequency of total pouch complication (86.7% versus 66.7%, P = 0.001), chronic pouch complication (68.4% versus 51.5%, P = 0.016), and chronic antibiotic-refractory pouchitis (16.3% versus 7.1%, P = 0.043). Multivariate logistic analysis showed that Area-M was an independent risk factor for chronic antibiotic-refractory pouchitis (odds ratio [OR]: 1.025; 95% confidence interval [CI]: 1.007–1.042, P = 0.005). The 22 patients with 2 or more pelvic MRI-DIXON scans were further classified into 2 groups by the change from the initial to latest MRI-DIXON scans. Patients with Area-M increase ≥10% and Area-M/height increase ≥10% were found to have shorter pouch survivals than those with increase <10%. Conclusions: A new method was established for measuring peripouch fat using pelvic MRI-DIXON-F image. Our study suggests that accumulation of peripouch fat may be associated with poor outcomes in selected IBD patients suspected of inflammatory or mechanical disorders of the pouch. Whether this association is causal warrants further investigation.